CLINICO-RADIOLOGICAL FINDINGS AND GENETIC ANALYSIS OF CHILDREN WITH HEREDITARY NEUROLOGICAL DISORDERS - Virk, Ahmad Omair; Zafar, Faisal; Sultan, Tipu (Pakistan Armed Forces Medical Journal, 2019)
Objective: To determine the clinical profile, radiological findings and genetic analysis of children with inherited neurological disorders. Study Design: Cross sectional study. Duration and Place of Study: Department of Neurology, The Children’s Hospital Lahore, from March 2013 to September 2016. Material and Methods: Ninety two patients upto 20 years of age were selected. Blood sample was taken from patients and both parents. Samples were tested for whole exome sequencing Results: There were 51% males. Age ranged from 5 months to 20 years. A total of 55.4% patients had developmental delay and 44.5% had neuroregression. Hearing impairment was found in 7.6% patients while vision was affected in 11.9%. Speech was affected in 66.3% patients while 43.4% patients had seizures. Autistic spectrum of disorders were observed in 20.6% patients. Microcephaly was seen in 19.5% cases. Out of 60 families, 23 (38.3%) had more than one offspring affected. Upper motor neuron signs were present in 50% patients while 15.2% patients had lower motor neuron signs. Leukodystrophy was seen in 19.5% patients. Cerebellar atrophy was observed in 15.2% patients while 17.3% patients had cerebral atrophy. Neuroimaging was normal in 34 patients. On genetic analysis, 48.3% families had known gene mutation while 51.6% families had novel gene mutation. Conclusion: Degenerative brain disorder (DBD) and Global developmental delay/intellectual disability (GDD/ ID) are entities with diverse clinical presentations. Whole exome sequencing is a helpful diagnostic tool. In addition to previously discovered genes, many novel genes have been identified.